Educação ambiental na escola estadual Dr. Joaquim Pereira da Costa – Gurupi - TO - Oliveira, Alessandro Lemos de (Universidade Federal do Tocantins, 2017)
Environmental education plays an important role in the human process of awareness regarding the use and maintenance of natural resources, the school is an ideal space for the development of actions with the students can contribute positively to the formation of these new generations. The aim of this study was to analyze the vision and participation of teachers and students related activities focused on environmental education. The survey was conducted in the State School Dr. Joaquim Pereira da Costa, located in the municipality of Gurupi - TO. The study involved 21 teachers and 168 of the 521 high school students, and 21 environmental monitors. The research was exploratory, with field and literature, and data collection conducted through specific questionnaires for teachers and students. To obtain these data the study was divided into 4 stages that took place between the months of April to October 2015, and the first step consisted of the survey of the actions carried out in the school focused on environmental education. In step 2 was the questionnaire of teachers being followed by step 3, which was the questionnaire of students. The completion took place to step 4, where it was applied a verification questionnaire level of environmental awareness of environmental monitors. The results with the teachers indicated that they believe the activities that have been conducted over the past few years the school has contributed to a better education of students regarding the environmental practices should these be maintained and improved. However teachers reported having difficulties to work issues related to environmental education due to the extensive curriculum and the lack of financial resources. Regarding students, they have shown to have a positive view on the way teachers work in environmental education room. The participation of students in school activities concentrated between lectures and seminars held throughout the year at school and at specific dates. Regarding environmental monitors, the results were considered positive, since the students involved as multipliers of the developed environmental activities shown to be aware of potential features and the environmental awareness of the tests to which they were submitted. Based on these results, both teachers, the students and environmental monitors have positive view on environmental activities at school, but it is emphasized that the participation of both need improvement.